Guidance: Islamic Character-Building Model at SMA Pribadi Bandung for Creating a Golden Generation - Setiawan, Fajar Sidik; Anwar, Saepul; Subakti, Ganjar Eka; Haris, Ahmad Abdul (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This study seeks to investigate the process of character development through character-building initiatives, guidance programs, and the diversity of students at SMA Pribadi Bandung Bilingual School, along with the implications for Islamic Education (PAI) instruction within the institution. The main research question addressed in this study is: How are the character building programs, guidance programs, and student diversity implemented at SMA Pribadi Bandung, and how does the Islamic character building model at SMA Pribadi Bandung contribute to the development of a golden generation? The research method employed is qualitative with a best-practice case study approach. Data were collected through in-depth interviews, observations, and documentation studies. The data analysis followed the latest Miles and Huberman model, which includes data condensation, data display, and drawing and verifying conclusions. The research findings indicate that the character building programs, guidance programs, and student diversity at SMA Pribadi Bandung Bilingual School have been implemented excellently, comprehensively, and thoroughly. These programs are not only designed to shape the character of students but also that of teachers and staff who participate in these programs. The presence of a dedicated committee along with the character building programs significantly impacts the essence of PAI learning, making it more relevant and meaningful for students as it closely relates to their experiences and understanding of Islamic character. This study aims to act as an impetus or a benchmark for other educational institutions to prioritize character-building initiatives within their frameworks. It highlights the understanding that schools function not solely as venues for knowledge dissemination but also as critical environments for character development.